(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
This study was conducted in the cloth canopy of the College of Agriculture, University of Basrah, during the growing season 2021-2022 on seedlings of kumquat and local lemon, totaling 54, 27 seedlings for each plant type, in three replications, as the seedlings were sprayed six times with three concentrations (0, 50, 100) mg l-1 of the amino acids tryptophan and glycine. The study results showed that using the two amino acids improved most of the anatomical characteristics of the seedlings of both types. The treatment with a concentration of (100 mg l-1) was recorded, and both acids had a significant superiority in the characteristics of cuticle layer thickness, epidermal layer thickness, tannin layer thickness, and columnar cell thickness at a rate of (19,000; 39.222; 39.444; 92.222) μM for tryptophan, respectively. The rates of glycine were (18.667, 33.778, 38.444, 83.889) μM, respectively, for kumquat seedlings, and the rate of tryptophan was (21.11, 44.67, 43.67, 112.33) μM, respectively, and the average of glycine was (20.33, 39.11, 42.78, 104.2) μM, respectively. For lemon seedlings, the interaction between the two acids had a significant effect, as the interaction treatment (100 mg l-1 tryptophan and 100 mg l-1 glycine) recorded the best results in the characteristics of cuticle layer thickness, epidermal layer thickness, tannins layer thickness, and columnar cell thickness (23,000; 45.000; 46.000; 99.667) μM, respectively, for kumquat seedlings, and the overlap for lemon seedlings was (25.00, 51.00, 51.00, 120.333) μM, respectively.